Regulation of a serine protease homolog by the JNK pathway during thoracic development ofDrosophila melanogaster. Issue 1 (7th February 2015) - Srivastava, Ajay; Dong, Qian
Abstract : The importance of the Jun N‐terminal Kinase (JNK) pathway during normal development and tumor invasion has been well documented in Drosophila . Here, this pathway plays important roles in epithelial morphogenesis, wound healing, apoptosis, immunity and regulation of lifespan. However, which downstream molecules facilitate these effects is not very well elucidated. In this study, data are presented on a serine protease homolog (SPH), scarface . These data show that scarface is under regulatory control of the JNK pathway and that this pathway is both necessary and sufficient for its expression within the context of thoracic development. Consequently, down‐regulation of scarface results in a thoracic‐cleft phenotype that phenocopies the JNK pathway defect. A possible role of scarface during thoracic development in Drosophila is discussed. Abstract : Scarface is up‐regulated in peripodial epithelium and peripodial stalk cells in wing disc. Overexpression of JNK pathway causes up‐regulation of scarface . Down regulation of JNK pathway results in down regulation of scarface . Scarface knockdown in wing disc phenocopies JNK pathway defect.